G461(P) Premature infants on long term ventilation: Impact of early referral on hospital length of stay. (24th May 2017) - Casanueva, L; Ray, S; Halley, G; Wakeman, R; Combes, J; Keating, J; Merrit, K; McClements, A; Goss, E
Abstract : Aim: Retrospective clinical audit to evaluate the impact of early referral to the Royal Brompton Children's Long Term Ventilation Service (RBH LTVS) of preterm infants dependent on respiratory support. Methodology: Retrospective analysis of all preterm infants referred to RBH LTVS and subsequently discharged home on long-term ventilation via tracheostomy (tr-LTV). Patients categorised as those referred before (Group I) and after (Group II) an active engagement process to encourage early referral, supported by specialist commissioners during 2012. Referral gives access to clinical support, web based discharge pathway, and regional education programme. The time from tracheostomy to referral, median hospital length of stay (LOS), and median LOS when medically 'fit for discharge' (FFD) from hospital, were measured and compared between the two groups using Kruskall Wallis test. Results: During the study period 42 ex-premature infants referred to RBH LTVS were discharged home on tr-LTV. Using tracheostomy as a surrogate marker of need for LTV, 70% of patients in Group II were referred within 30 days of tracheostomy, compared with only 46% in Group I. The median LOS reduced from 461 (355–540) days in Group I to 339 (282–435) days in Group II (p=0.02) with greatest impact on FFD LOS, reduced from 226 (109–305) to 41 (29–130) days (p=0.001). The average number of hospital days when a patient was medically 'fit for discharge' reduced from average of 221 to 93. The total duration of intensive care stay was 335 (IQR 259– 418) days in Group I and 315 (IQR 260–379) days, which was not statistically significant (p=0.47). Conclusions: Enabling early referral of preterm infants dependent on respiratory support to a specialised LTV service can significantly reduce hospital length of stay, particularly when the child is medically fit for discharge. There was no change in the number of ICU days per patient indicating no change in the underlying population's dependence on critical care.